2013
DOI: 10.2478/aoa-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Induced Hearing Loss in Professional Orchestral Musicians

Abstract: The overall purpose of this study was to assess hearing status in professional orchestral musicians. Standard pure-tone audiometry (PTA) and transient-evoked otoacoustic emissions (TEOAEs) were performed in 126 orchestral musicians. Occupational and non-occupational risk factors for noise-induced hearing loss (NIHL) were identified in questionnaire inquiry. Data on sound pressure levels produced by various groups of instruments were also collected and analyzed. Measured hearing threshold levels (HTLs) were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
(15 reference statements)
2
11
0
2
Order By: Relevance
“…The prevalence of notches at 6000 Hz in the control group is not surprising since according to the Nord-Trøndelag Hearing Loss Study [31] such notches were observed both in unscreened and screened for a history of noise exposure and ear-related disorders and diseases populations of men and women up to 40 years old. Moreover, some earlier studies in musicians, including professional orchestral musician, have also shown high frequency notches (mainly at 6000 Hz) in audiograms [7,9,10]. Similar outcomes have been also obtained for younger (student) musicians [18,19].…”
Section: Disscusionsupporting
confidence: 71%
See 2 more Smart Citations
“…The prevalence of notches at 6000 Hz in the control group is not surprising since according to the Nord-Trøndelag Hearing Loss Study [31] such notches were observed both in unscreened and screened for a history of noise exposure and ear-related disorders and diseases populations of men and women up to 40 years old. Moreover, some earlier studies in musicians, including professional orchestral musician, have also shown high frequency notches (mainly at 6000 Hz) in audiograms [7,9,10]. Similar outcomes have been also obtained for younger (student) musicians [18,19].…”
Section: Disscusionsupporting
confidence: 71%
“…Furthermore, Fearn [18] has estimated that students spent on average 10-35 h/week on playing musical instruments and additionally performed in orchestras for 2−3 h 56 times/year. For comparison, Pawlaczyk-Łuszczyńska et al [10] have found that professional orchestral musicians were usually exposed to music for 7-70 h/week (average 30 h/week) due to both on-the-job and off-the-job playing. Therefore, it is not surprising that Phillips et al [19], when analyzing the prevalence of hearing impairment in student musicians (aged 18−25 years), have found typical NIHL notches (occurring mainly at 6000 Hz) in 45% of 329 students.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These exposures vary considerably over time, and strongly depend on the repertoire. In order to illustrate the levels of noise, to which the musicians are exposed while playing instruments, the Table 1 presents aggregate results of measurements of sound pressure levels at positions of musicians playing various instruments [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…The L EX,w values were estimated based on the results of our previous studies [9][10][11] and on a weekly time of playing an instrument declared by musicians. This table also presents data on the A-weighted noise exposure level during analyzed rehearsals (between TEOAE tests) normalized to a nominal 8-h working day (L EX,8h ).…”
Section: Resultsmentioning
confidence: 99%